Strengthening the Capacity of Village Apparatus in the Implementation of Public Administration Policies in Pejeng Village, Gianyar Regency - Wirantini, Ni Kadek Ayu; Juniasa, I Dewa Nyoman; Yunita, I Made; Kusumaningrat, Cokorda Istri Mas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the strengthening of village apparatus capacity in the implementation of public administrative policies in Pejeng Village, Gianyar Regency. The background of this research lies in the strategic role of village apparatus in ensuring effective and accountable village governance policies, as well as the challenges encountered in the implementation of public administration at the village level. The research employed a mixed methods approach, with data collection conducted through questionnaires administered to 60 village officials, in-depth interviews with 10 key informants, and document analysis. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically analyzed to identify patterns in the experiences of village officials in carrying out their duties. The findings indicate that the capacity of village apparatus—including technical competence, regulatory understanding, and managerial skills—significantly influences the effectiveness of public administrative policy implementation. The results also reveal that ongoing training, adequate resource support, and well-structured supervision systems are key determinants of successful implementation. The study concludes that strengthening village apparatus capacity not only improves administrative performance but also reinforces the legitimacy of public policies at the local level. The policy implications emphasize the need for integrated interventions between the district, provincial, and village governments to sustainably enhance the competency of village apparatus.